Chemoradiation of locally advanced squamous cell carcinoma of the head-and-neck (LASCCHN): Is 20 mg/m2 cisplatin on five days every four weeks an alternative to 100 mg/m2 cisplatin every three weeks?. (August 2016) - Rades, Dirk; Seidl, Daniel; Janssen, Stefan; Bajrovic, Amira; Hakim, Samer G.; Wollenberg, Barbara; Karner, Katarina; Strojan, Primoz; Schild, Steven E.
Highlights: 5 × 20 mg/m 2 cisplatin every four weeks was better tolerated than 100 mg/m 2 every three weeks. 100 mg/m 2 cisplatin was not superior to 20 mg/m 2 cisplatin regarding LRC, MFS and OS. Chemoradiation with 5 × 20 mg/m 2 every four weeks appears preferable. Summary: Objectives: To compare chemoradiation with 100 mg/m 2 cisplatin every three weeks to 20 mg/m 2 on five days every four weeks for locally advanced squamous cell carcinoma of the head-and-neck (LASCCHN). Materials and methods: In 230 patients receiving chemoradiation for LASCCHN, 100 mg/m 2 cisplatin every three weeks ( N = 126) and 20 mg/m 2 cisplatin on five days every four weeks ( N = 104) were retrospectively compared. Chemoradiation plus eleven characteristics (T-/N-classification, performance score, gender, age, tumor site, grading, surgery, radiation technique, pre-chemoradiation hemoglobin, cumulative cisplatin dose) were analyzed for locoregional control (LRC), metastases-free survival (MFS) and overall survival (OS). Chemoradiation groups were compared for adverse events. Results: On univariate analyses, chemoradiation had no impact on LRC ( p = 0.53), MFS ( p = 0.67) and OS ( p = 0.14). On multivariate analysis of LRC, T-classification ( p = 0.045) and hemoglobin ( p < 0.001) were significant. On multivariate analysis of MFS, performance score ( p = 0.028) was significant. On multivariate analysis of OS, performance score ( p = 0.009) and hemoglobin levels ( p = 0.002) achieved significance. Chemoradiation with 100 mg/m 2 cisplatin was associated with more pneumonia/sepsis ( p = 0.003), grade ⩾2 nausea/vomiting ( p < 0.001), grade ⩾2 nephrotoxicity ( p = 0.005), grade ⩾2 xerostomia ( p = 0.002), grade ⩾3 hematotoxicity ( p = 0.052) and grade ⩾2 ototoxicity ( p = 0.048). Concluding statement: 20 mg/m 2 cisplatin on five days every four weeks was associated with fewer adverse events than 100 mg/m 2 cisplatin every three weeks. 100 mg/m 2 cisplatin was not significantly superior to 20 mg/m 2 cisplatin regarding LRC, MFS and OS. Given the limitations of a retrospective study, 20 mg/m 2 cisplatin appeared preferable. The results should be confirmed in a randomized trial.